On piecewise smooth vector fields tangent to nested tori - Carvalho, Tiago [UNESP]; Teixeira, Marco A. (Elsevier, 2016)
In this paper we present a number of results involving 3D nonsmooth dynamical systems tangent to a foliation. We study one-parameter families of systems Zε passing through a specific model Z0 whose phase portrait is foliated by invariant nested tori. For each positive integer k we, explicitly, construct a family Zε k possessing exactly k nested tori.
Keywords: Bifurcation; Invariant tori; Limit cycles; Nonsmooth vector field